Método para a identificação de oportunidades potenciais de desenvolvimento de novos artefatos e produtos - Kampa, Josmael Roberto (2019)
As a means to succeed in their investments, innovation is both a prerequisite and a challenge for entrepreneurs of this time. Innovating involves generating offers that make the preexisting ones obsolete, which implies in the creation or recognition of new forms of differentiation, the Opportunities Identification (OI). These may be due, among other, to new solutions or new problems to be solved, which is a less explored path in the New Product Development process (NPD). There are studies aimed at systematizing OI, but present a discreet behavior in front of intuitive approaches which relies on individual talent, a non-unanimous resource. Being the innovation time sensitive, there is room for artificial stimuli to intuition. In this way, the investigation opportunity is identified and a general research question can be formulated: what and how should the OI be done to improve the success of the NPD? To answer this research has as objective: to develop a method (model and its support) that stimulates the intuitive and/or systematic identification of potential opportunities of new products development as problems. In this prescriptive and artificial science study was adopted the methodological structure Design Research Methodology (DRM), philosophically aligned with pragmatism. The developed model is supported by textual expositions, schemas, guidelines and tools integrated in a manual for self-learning. Different representations are provided for the easy memorization and close employment as a continuous habit. This simplifies the author’s previous systematic approach and broadens it with intuitive search. The current support presents completeness and internal consistency and shown applicable in the demonstrated cases. It leads to problems that can feed the Front End of Innovation (FEI) and NPD.